WANITA (NYAIE) DALAM NOVEL BUNGA ROOS DARI CIKEMBANG KARYA KWEE TEK HOAY - Septiani, Nur Alifah; Pramono, Dedi (MIMESIS, 2022)
Over 90 years (1870-1960), 800 authors published 3000 Chinese Malay erudite workshops. Bunga Roos from Cikembang is one of the most well-known workshops. The work was written by Kwee Tek Hoay, one of the most prolific authors of his day. Bunga Roos from Cikembang, similar to the previous Chinese Malay literary work, casts an indigenous womanish figure as a Chinese man's "nyaie." The distinction in this tale is that the "nyaie" is elevated to a higher status. She is no longer referred to as a "mistress" (a libido grater), but rather as a lady by her master, even though she has never been married. This distinction is noteworthy and warrants additional investigation. The goal of this research is to locate honorable examples for the female character who becomes the "nyaie" in a detail in this sense, the study theory employed a gender theory, specifically Richard A. Lippa's notions of nature and nurture. This research is the outcome of a library search. The data analysis was done in a descriptive-qualitative manner. Marsiti, like a lady"nyaie" (concubine) of a high-class Chinese, was lauded not only as a woman who satisfies her master's lust because of her beauty, sexiness, and service (nature) but also as a woman in a good social arrangement (nurture). Marsiti is seen as a "partner" who can be relied upon to help the master think through the various challenges that arise in his life as a result of his wimpiness, intelligence, and fidelity. In this case, the location of the woman "nyaie" in Kwee Tek Hoay's Cikembang Bunga Roos appears to be superior to the previous work.